Simulating airport operations using different world views - Faboya, Olusola Theophilus (2013)
An airport is a large complex socio-technical system with different stakeholders and different need. Due to its complexity, Operations Research (OR) techniques have been useful aids when it comes to understanding and improving the operations of an airport. However, there are several existing modelling studies in air transportation industry, but not all areas of airport operations problems have been resolved. Even some of the ones modelled have found to be limited in level of details used in defining the system components. The aim of the dissertation is to find new modelling application areas for airport operations. To achieve this, we investigated the level of details used in defining the existing models systems' components (world view) from literature review, and classified the models based on their levels of abstraction. Gaps were found, and two areas were chosen as case studies where models were built as proof-of-concepts to investigate the feasibility of their applications in airport. Case study 1 is modelling airport maintenance scheduling using agent-based paradigm as an alternative method instead of the commonly used mathematical techniques. While case study2 focussed on modelling airport marketing strategy using system dynamics paradigm. In the course of this study, we maintained constant interactions with some experts who are knowledgeable in airport operations, they verified and validated various stages of the models development, this enabled us not to treat any of the important components of the systems we are modelling as exogenous and gave reasonable estimates for the models experimentation. Finally, they validated the results of the models (experimental validation) and the behaviours observed, and found the models useful and applicable in airport operations.